Correlation Isocitrate Dehydrogenase Level and Triglyceride Level in Rats Stimulated with Ethanol Extract of Moringa Leaf: Hubungan Kadar Isositrat Dehidrogenase dengan Kadar Trigliserida pada Tikus yang Distimulasi dengan Ekstrak Etanol Daun Kelor - Fitriana Sari, Devi; Wulandari, Devyana Dyah; Wardany, Nadya Ika; Baskara, Muhamad Damar; Nadzarillah, Najmatul Jannah (Universitas Muhammadiyah Sidoarjo, 2024)
Food substances are oxidized through mitochondria to produce chemical energy in the form of adenosine triphosphate (ATP), which is used as energy. The Krebs cycle uses the energy produced by the body to make adenosine triphosphate. A class of enzymes known as dehydrogenases including isocitrate dehydrogenase (IDH) is responsible for electron transport from substrate to electron receiver. In addition, IDH is involved in various cellular processes, including lipogenesis, which is part of lipid metabolism. This study aimed to investigate the relationship between triglyceride (TG) levels and mitochondrial IDH enzyme activity with respect to taking ethanol extract of Moringa oleifera leaves. This type of research is experimental with a control group design. The samples in this study were 20 white rats divided into 5 treatment groups, namely Negative Control (K-) rats with normal conditions, Positive Control (K+) rats with tired conditions, Standard Group (STD) rats with creatinine drug induction, Treatment 1 (P1) rats given 250 mg/kgBB dose of Moringa oliefera leaf extract, Treatment 2 (P2) rats given 500 mg/kgBB dose of Moringa Oliefera leaf extract. The results of statistical analysis of the correlation test p value 0.147 ≥0.05 can be concluded that there is no relationship between IDH enzymes and TG.